Polarons are probes of the dynamic nanoscale environments found in electrochemically doped π-conjugated polymers - Megan R. Brown; Zhiting Chen; Arianna Magni; Hong Li; Joel H. Bombile; Sa Suo; Tianquan Lian; Michele S. Myong; Jean-Luc Bredas; Matthew J. Bird; Neal R. Armstrong; Alberto Salleo; et al. (Proceedings of the National Academy of Sciences, 2026)
Charge carriers (i.e., polarons) in electrochemically doped organic (semi)conductors are proposed to be regulated by several physicochemical features, including the chemical compositions and structures of the π-conjugated frameworks of the semiconductor building blocks, the chemistry of the electrolyte (considering both the salt and solvent), multiscale and time-dependent morphology variations across the material as a function of electrochemical processes, and assorted permutations of these and other factors. To address these hypotheses, we investigate the energetic, optoelectronic, chemical, and local structural properties of negative polarons (radical anions) as a function of electrochemical doping in the donor–acceptor, π-conjugated redox copolymer P(NDI2OD-T2), also referred to as N2200. A critical finding is that there is not just “one type” of polaron in electrochemically doped P(NDI2OD-T2). Rather, an ensemble of polarons exists, with the polarons having optoelectronic signatures that are defined by their nanoscale environments. Importantly, the polaron optical signatures serve as local probes for how the operando electrochemical environments are dynamically working in concert to facilitate charge transport. Collectively, the distinctive and extensive integration of theory and measurement science presented here establishes a baseline for the roles that semiconductor and electrolyte chemistries and dynamic structural features have on polarons in electrochemically doped organic semiconductors and how these factors influence the energetics and rates of polaron transport.